Freedom as Morality - (:unkn) unknown (My University, 2014)
In this paper, I offer a reading concerning Kant's concept of freedom and its relation to morality. In Groundwork III, Kant deduces morality from freedom, such strategy in which requires a metaphysical understanding of freedom. However, according to Kant's argument in the first Critique, we do not have knowledge of freedom as an idea of reason. That is: we cannot know that we are free. In the second Critique, Kant clams that morality is a "fact of reason", which is not dependent on any antecedent data. We could cognize that we are free when we are conscious of the moral law. In this paper, I do some preliminary work regarding this argumentative shift in Kant's moral philosophy. I reconstruct Kant's arguments in the Groundwork III and the second Critique to show that freedom as an idea of reason gains its reality from a practical standpoint view.